Facile and low-cost synthesis of PEDOT:PSS/FTO polymeric counter electrode for DSSC photosensor with negative capacitance phenomenon - Shenouda, S. S.; Yahia, I. S.; Hafez, Hoda S.; Yakuphanoğlu, Fahrettin (Iop Publishing Ltd, 2019)
In this research, PEDOT:PSS film is employed as a counter electrode in the dye-sensitized solar cell (DSSC) for low-cost photo-sensing applications. This DSSC is based on nanostructured TiO2 as photoanode. The morphology of the counter electrode was examined using atomic force microscope showing well distributed spherical clusters with average size 214.04 nm. This DSSC behaves like Schottky diode in the dark condition with rectification ratio 40 at 0.5 V. The photovoltaic behavior was studied in the light intensity range 10-130 mW cm(-2). This solar cell has a stable fill factor (about 0.5) for most of the studied illumination intensity range. The photo-response of the current suggests that the new designed DSSC with the polymeric counter electrode is a promising device for low-cost photosensor. The cell shows capacitance inversion from positive to negative with increasing the applied frequency at about 100 kHz which recommends this cell for further applications. Also, the effect of frequency on the built-in potential and the series resistance has been investigated.
Keywords: DSSCs; PEDOT:PSS; photosensor; photovoltaic; polymeric counter electrode; conduction mechanism